2021
DOI: 10.1177/08853282211016934
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo study on the osseointegration of magnesium and strontium ion with two different proportions of mineralized collagen and its mechanism

Abstract: To explore the optimal combination of Mg2+, Sr2+ and mineralized collagen (nHAC) with two different proportions of hydroxyapatite (HA) and collagen (COL) on differentiation of MC3T3-E1 and the underlying mechanism, as well as achieve bone osseointegration. MC3T3-E1 cells were cultured in a complete medium with Mg2+ at the concentration of 0, 4, 8, 12, 16, 20 mmol/L, Sr2+ at the concentration of 0, 3, 6, 12 mmol/L, and the impregnation solution of 3:7 and 5:5nHAC. The differentiation of MC3T3-E1 was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…The content of Mg in the composite and the sustained release of Mg too high and too low will affect its bone repair effect. Sun et al [ 54 ] found that MC3T3-E1 cells significantly promoted Runx-2, OCN and BMP-2 gene expression when cultured in a medium containing 12 mmol/l Mg 2+ . Therefore, when the Mg content in the implantation site of the composite is close to that in 12 mmol/ Mg 2+ medium, it can significantly promote the osteogenic properties of the scaffold.…”
Section: Osseointegration Of MC and Metal Elementsmentioning
confidence: 99%
See 4 more Smart Citations
“…The content of Mg in the composite and the sustained release of Mg too high and too low will affect its bone repair effect. Sun et al [ 54 ] found that MC3T3-E1 cells significantly promoted Runx-2, OCN and BMP-2 gene expression when cultured in a medium containing 12 mmol/l Mg 2+ . Therefore, when the Mg content in the implantation site of the composite is close to that in 12 mmol/ Mg 2+ medium, it can significantly promote the osteogenic properties of the scaffold.…”
Section: Osseointegration Of MC and Metal Elementsmentioning
confidence: 99%
“…In vivo studies have found that the MHA/Coll scaffold is effective in recruiting progenitors and osteocytes and contributes to the assembly of the hematopoietic ecosystem. Sun et al [ 54 ] demonstrated that MC scaffolds loaded with Mg–Sr ions could activate PI3K/AKT/GSK3b/b-catenin signaling pathway to promote osteogenic differentiation of cells. So the MHA/Coll scaffold has good osteoinductive potential and provides a direction for clinical bone repair.…”
Section: Osseointegration Of MC and Metal Elementsmentioning
confidence: 99%
See 3 more Smart Citations